Purkhyauli Thalo: Me and My Auto Ethnographical Study - Subedi, Ram Prasad (Pargatishil Darpan, 2024)
The main purpose of this article is to connect my personal experience with social meaning. This article presents my personal experience as a story. In this auto ethnography knowledge production, I present myself and my own particular experience as an analytical narrative. Through this auto ethnography, I have once again connected with the world I lived in and the vivid experiences there through interaction. As a person is a social being, he learns social customs, values and conduct from the elders of the society and the person himself is the source of social information for him. I have taken as a source of information what I have learned directly from the society that brought me up, what I have seen and experienced and who I have interacted with. From the study area, I have received information from people who have lived in different places in the country and abroad through phone interactions and meetings. I have prepared this auto ethnography article by including the social experiences of my mother who raised me and her life stories as a source of information. People are bound by the customs of society. In this auto ethnography exploring social and its associated customs, it becomes apparent that certain rituals once imbued with significance by our ancestors may how imped societal progress. While these rituals held meaning in their time, their contributed practice poses challenges to the advancement of our community. It seems that there is a need for change in the rituals that have been going on like that. There is a need for a progressive change in the traditions that are the hindrances to the development of such old societies. The conclusion of this article is that there is a need for progressive change in the old social injustices based on caste, gender and color.